A novel method to extend viability and functionality of living heart slices - Ross, Abigail J.; Krumova, Iva; Tunc, Berfin; Wu, Qin; Wu, Changhao; Camelliti, Patrizia (Frontiers in Cardiovascular Medicine, 2023)
Living heart slices have recently emerged as a powerful experimental model for fundamental cardiac research. By retaining the structure and function of the native myocardium while maintaining the simplicity of cell culture models, heart slices can be easily employed in electrophysiological, pharmacological, biochemical, and structural investigations. One single heart yields many slices (>20 slices for rodents, >100 slices for porcine or human hearts), however due to the low throughput of most assays and rapid slice degeneration within 24 h of preparation, many slices remain unused and are discarded at the end of the preparation day. Here we present a novel method to extend viability and functionality of living heart slices, enabling their use in experiments over several consecutive days following preparation. By combining hypothermic conditions with inhibition of myosin II ATPase using 2,3-butanedione monoxime (BDM), slices prepared from the left ventricle of porcine hearts remain viable and exhibit preserved contractile function and morphology for up to 6 days. Electrophysiological function was also confirmed over the 6 days by extracellular field potentials recordings. This simple method not only maximizes the use of slices prepared from one single heart, thus reducing the number of animals required, but also increases data reproducibility by allowing multiple electrophysiological, pharmacological, biochemical, and structural studies to be performed from the same heart.